KEPENTINGAN INDONESIA DALAM EKSPOR KAKAO KE AMERIKA - Lestari, Indah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research discusses about “Indonesia’s Interest In Cocoa Exportsto United States”. The purpose is this research is to find out why Indonesia cooperates with the United Stetes in Cocoa Exports. Cocoa is a leading commodity where Indonesia is a producer country thirdly after Ivory Coast and Ghana. Indonesia have the potential to become the world’s major Cocoa producers if the main problems in Cocoa such as low product and product quality can be overcome and Cocoa agribusiness is well developed and managed. Indonesia still has a potential land of millions of hectares that has not been utilized optimally.This is qualitative research which used descriptive explanative methods, and collecting datas from books, journals, articles, mass media, official ublications and relevant websites. This paper used the liberalism perspective written by Adam Smith, analysis unit nation-state and the theory is International Corporation written by K.J.Holsti.The result of the research is Indonesia export Cocoa to America because America is the world’s biggest Cocoa consumers. America is the destination country for Indonesian Cocoa exports after Malaysia. America has the largest Chocolate company of the world, such as : Berdex International, Blomer Chocolate, Pacon Express, Cocoa Barry US Inc, Van Leer Chocolate Inc, General Cocoa, Nestle, dan Prudent Trading.Key words : Export duty, Indonesian National Standard, International Corporation, Liberalism perspective